LAW ENFORCEMENT DUE TO VIOLATION LAW NUMBER 6 OF 2018 ABOUT QUARANTINE (Study of Decision No. 173/PID.SUS/2021/PTDKI, NAME HABIB RIZIEQ SHIHAB) - Muhammad Tedy; Ismed Batu Bara (SEAN Institute, 2022)
Currently residents are faced with a new variant of the virus originating from the city of Wuhan, China. This virus emerged in 2019 under the name Corona Virus Disease 2019 or better known as COVID-19, where this virus is an infectious disease that attacks the respiratory tract with symptoms of fever, cough and shortness of breath.According to Law Number 6 of 2018 concerning Health Quarantine, it is an effort to prevent and ward off the exit or entry of diseases and/or public health risk factors that have the potential to cause public health emergencies. The implementation of PSBB and Quarantine is an effort of a health emergency (Law Number 6 of 2018). The formulation of the problem in this paper are: 1. What is the scope of health care arrangements in Indonesia? 2. How is the application of the law to cases of violations of health protocols? This legal research method is normative juridical, namely research to be carried out to obtain materials in the form of theories, concepts, legal principles and legal regulations related to the subject matter.